Targeting histone deacetylase SIRT1 selectively eradicates EGFR TKI-resistant cancer stem cells via regulation of mitochondrial oxidative phosphorylation in lung adenocarcinoma - Sun, Jiangtao; Li, Guifang; Liu, Yiwen; Ma, Mingyang; Song, Kaifang; Li, Huaxu; Zhu, Daxing; Tang, XiaoJun; Kong, Jinyu; Yuan, Xiang (Neoplasia (New York, N.Y.), 2020)
Lung adenocarcinoma (LAD) is a human malignancy successfully treated with the tyrosine kinase inhibitor (TKI) gefitinib; however, the enrichment of therapy resistant cancer stem cells (CSCs) in such patients is assumed to be a source of treatment failure. Evaluation of LAD cell populations treated with the TKI inhibitor gefitinib identified unique aspects of a subpopulation of tumor cells exhibiting stem-like properties and mitochondria-specific metabolic features along with their reliance on sirtuin 1 (SIRT1) for survival advantage. This addiction to bioenergetic metabolism in LAD treated with EGFR-targeted therapy suggests that mitochondrial targeting should be synthetically lethal using established cytotoxic therapies. Accordingly, loss of the phenotype present in resistant CSC clones either by targeting the energy metabolism with tigecycline, a mitochondrial DNA-translation inhibitor, or tenovin-6 (TV-6), a SIRT1 inhibitor, inhibited their dependency on mitochondrial oxidative phosphorylation (mtOXPHOS) and sensitized them for a more pronounced and long-lasting TKI therapeutic effect. The results specifically demonstrated that combined therapy with TV-6 and gefitinib resulted in tumor regression in xenograft mouse models, whereas administration of a single agent showed no such efficacy. Importantly, combined treatment with TV-6 also decreased the effective dose of gefitinib necessary for treatment response. Clinical analysis demonstrated that high-profile SIRT1 and mtOXPHOS proteins were associated with recurrence and poor prognosis in LAD patients. These observations support the CSC hypothesis for cancer relapse and advocate use of mitochondria-targeting inhibitors as part of combinatorial therapy in a variety of clinical settings, as well as for reducing first-line TKI dosage in LAD patients.